2016
DOI: 10.1128/iai.00708-16
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Agonist Pam3CSK4 Alleviates the Pathology of Leptospirosis in Hamster

Abstract: dLeptospirosis, caused by pathogenic spirochetes, is a zoonotic disease of global importance. The detailed pathogenesis of leptospirosis is still unclear, which limits the ideal treatment of leptospirosis. In this study, we analyzed the expression of Toll-like receptor 2 (TLR2) and TLR4 in target organs of both resistant mice and susceptible hamsters after Leptospira interrogans serovar Autumnalis infection. TLR2 but not TLR4 transcripts in mouse organs contrasted with delayed induction and overexpression in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…Up-regulation of IL-10 by leptospires would dampen the IFN-g expression, which would limit the bacterial clearance, hence favoring a chronic infection. Interestingly, it has recently been shown that the IL-10 secretion in the kidneys relies on the TLR2 pathway triggered by leptospires [49]. These data should encourage novel strategies aimed at enhancing phagocytic activity to avoid or limit leptospiral colonization in kidneys.…”
Section: How L Interrogans Establish Renal Chronicity?mentioning
confidence: 91%
“…Up-regulation of IL-10 by leptospires would dampen the IFN-g expression, which would limit the bacterial clearance, hence favoring a chronic infection. Interestingly, it has recently been shown that the IL-10 secretion in the kidneys relies on the TLR2 pathway triggered by leptospires [49]. These data should encourage novel strategies aimed at enhancing phagocytic activity to avoid or limit leptospiral colonization in kidneys.…”
Section: How L Interrogans Establish Renal Chronicity?mentioning
confidence: 91%
“…IL-10, unlike cytokines such as IL-1 and IL-12, is known to reduce inflammation via TLR-pathway downregulation and can therefore assist in combatting the spirochetal infection as well as any possible chronic effects such as arthritis (76, 77). The above was confirmed in recent mice studies that utilized a TLR2 agonist, Pam3CSK4, to induce IL-10 production which attenuated inflammatory response to Leptospira (78). Thus, spirochetal lipoproteins exert their pro-inflammatory effects through several pathways including CD14, TLR, and NF-κB signaling and induce both pro-inflammatory (such as IL-1) and anti-inflammatory cytokines (IL-10) production in myeloid cells such as M/M.…”
Section: Modulatory Effects Of Spirochetal Lipoproteins Related To Acmentioning
confidence: 57%
“…Recently, it has been shown that IL-10 was decreased in TLR2ko mice infected with leptospires [37] , suggesting that TLR2 activation leads to IL-10 production and would thus be crucial to favor the renal colonization by leptospires. Therefore, TLR2 would exert a dual role ( Fig.…”
Section: Host Innate Immune Determinants Important To Control the Dismentioning
confidence: 99%
“…2 ). On the one hand, TLR2 plays a protective role, being involved in the production of protective antibodies and cytokines and/or helping the host to survive the acute phase of leptospirosis when activated by a synthetic agonist [37] , but, on the other hand, it sustains the leptospires' ability to escape the immune response and survive, hidden in the kidney.…”
Section: Host Innate Immune Determinants Important To Control the Dismentioning
confidence: 99%